2020
DOI: 10.1186/s13020-019-0282-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Loureirin B on Crohn’s disease rat model induced by TNBS via IL-6/STAT3/NF-κB signaling pathway

Abstract: Background: Crohn's disease (CD) is a chronic relapsing form of inflammatory bowel disease, seriously threatening human beings health. However, the pathogenesis of CD is still unclear and there is no specific effective drug for treatment of CD. Resina Donis (RD) obtained from Dracaena cochinchinensis (Lour.) S. C. Chen (Liliaceae), has been used for the treatment of CD clinically. Loureirin B (LB) is one of the most important chemical compositions and physiologically active ingredients of resina draconis. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…In DSS-induced colitis in female mice, transplantation of male bone marrow-derived mesenchymal stem cells caused regeneration of colon E-cadherin expression indicating restoration of mucosal permeability (Sun et al., 2015 ). In TNBS-induced Crohn's-like colitis in rats, there was a remarkably down-regulated expression level of E-cadherin and increased apoptosis (Sun et al., 2020 ). In rats with TNBS-induced colitis, MPO activity got its maximum on days 7 and 10 post-induction and was consistent with the up-regulation of MMP-9 in peripheral and colonic neutrophils which modulates transmural colonic damage (Medina et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In DSS-induced colitis in female mice, transplantation of male bone marrow-derived mesenchymal stem cells caused regeneration of colon E-cadherin expression indicating restoration of mucosal permeability (Sun et al., 2015 ). In TNBS-induced Crohn's-like colitis in rats, there was a remarkably down-regulated expression level of E-cadherin and increased apoptosis (Sun et al., 2020 ). In rats with TNBS-induced colitis, MPO activity got its maximum on days 7 and 10 post-induction and was consistent with the up-regulation of MMP-9 in peripheral and colonic neutrophils which modulates transmural colonic damage (Medina et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…After incubation with the primary antibodies at 4 °C for 12 hours, secondary antibodies IgG (ab6721; Abcam; 1:1000 dilution) were applied to slides for an hour at room temperature. The sections were colored with a diaminobenzidine kit followed by counterstaining with hematoxylin and were examined by a light microscope (Sun et al., 2015 ; t al., 2020 ). For MMP-9 immunostaining, the sections were probed with rabbit and mouse monoclonal anti-MMP-9 (1:150 dilution), detected with sheep anti-rabbit or anti-mouse IgG fluorescein isothiocyanate (1:500 dilution), and examined under a fluorescent microscope (Baugh et al., 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, loureirin B remarkably ameliorated TNBS-induced inflammatory response via regulation of cytokines in the colonic tissues, and inhibited apoptosis through regulation of IL-6/STAT3/NF-κB signaling pathway. This finding may represent a novel approach to treat CD and provides an alternative choice for disorders associated with CD [70]. Homoisoflavans 69 and 7,10-dihydroxy-11methoxydracaenone (structure 103 in Figure 15) were isolated from a CHCl3 extract of the plant.…”
Section: Dracaena Cochinchinensis (Lour) Sc Chenmentioning
confidence: 95%
“…Meksuriyen and Cordell isolated loureirins A-D (structures 93-96 in Figure 15) from the leaves of the plant collected in Thailand [69]. Loureirin D (96) exhibited mild inhibition of LPS-stimulated NO production in RAW 264.7 macrophages, with an IC 50 value of 50.3 µM, whereas it inhibited the activation of the IL-6/STAT3/NF-κB signaling pathway [48,70]. Ichikawa et al isolated loureirins B (94) and D (96), 4,4 -dihydroxy-2,6-dimethoxydihydrochalcone (97), 2,4 -dihydroxy-4,6-dimethoxydihydrochalcone (98), 3,5,7-trihydroxy-4 -methoxyhomoisoflavanone (eucomol), 5,7,4 -trihydroxyhomoisoflavanone, and 7,4 -dihydroxy-5-methoxyhomoisoflavanone from the stem wood of the plant, a Thai folkloric medicine called "Chan-daeng" [71].…”
Section: Dracaena Loureiri Gagnepmentioning
confidence: 99%
“…Loureirin B (LrB) is a kind of flavonoid separated from sanguis draxonis. Sun et al found that LrB can attenuate the inflammation in an experimental inflammatory bowel disease model of rats [ 12 ]. Bai et al reported that LrB inhibits fibroblast proliferation and extracellular matrix deposition in the scar tissue of rabbits [ 13 ].…”
Section: Introductionmentioning
confidence: 99%